台灣老人營養狀況與認知衰退之關聯性探討 - 黃純甄(Chuen J. Huang); 蔡仲弘(Alan C. Tsai) (台灣公共衛生雜誌, 2013)
Objectives: To investigate the association of nutritional status and cognitive status and to identify a possible causal role of nutritional status in the future risk of cognitive decline in older Taiwanese. Methods: The study analyzed the 1999 and 2003 datasets of the ”Survey of Health and Living Status of the Elderly in Taiwan”. Subjects were interviewed, face-to-face, with a structured questionnaire. The Mini Nutritional Assessment (MNA) was used to rate nutritional status and the Short Portable Mental Status Questionnaire (SPMSQ)、was used to rate cognitive status. This cross-sectional study included 2,672 elderly at baseline while the longitudinal analysis included the 1895 subject who survived in 2003, less those who had severe cognitive impairment at baseline and those who failed to complete the 2003 interview. Both models controlled for socio-demographic factors, lifestyle, food intake, and health and medical conditions. Results: In regression models that controlled for possible confounders, cross-secti